2008
DOI: 10.1002/hep.22491
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 suppresses hepatitis C virus replication and increases resistance of hepatocytes to oxidant injury

Abstract: C hronic hepatitis C virus (HCV) infection is a worldwide health problem that can lead to chronic hepatitis, cirrhosis, and end-stage liver disease. 1 The virus has a plus-stranded RNA genome with a single long open-reading frame containing 5Ј and 3Ј flanking nontranslated nucleotide regions that are important for translation and replication. Although wild-type virus grows poorly in cell culture, 2 the development of subgenomic and full-length HCV replicons that stably replicate HCV RNA in permissive human hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 47 publications
(78 reference statements)
6
99
1
Order By: Relevance
“…They reported that increased expression of HO-1 is associated with diminished HCV replication and also with an increase of the resistance of hepatocytes to oxidative damage. Based on this findings, heme oxygenase regulation could be useful as an adjunctive antiviral therapy [62][63][64] .…”
Section: Heme Oxygenase Regulationmentioning
confidence: 88%
See 1 more Smart Citation
“…They reported that increased expression of HO-1 is associated with diminished HCV replication and also with an increase of the resistance of hepatocytes to oxidative damage. Based on this findings, heme oxygenase regulation could be useful as an adjunctive antiviral therapy [62][63][64] .…”
Section: Heme Oxygenase Regulationmentioning
confidence: 88%
“…There are some reports regarding to modulation of antioxidant enzymes as a HCV therapy, Zhu et al [62] worked with HO which catalyzes the rate-limiting reaction in the catabolism of heme which produces equimolar amounts of biliverdin, carbon monoxide and free iron. They reported that increased expression of HO-1 is associated with diminished HCV replication and also with an increase of the resistance of hepatocytes to oxidative damage.…”
Section: Heme Oxygenase Regulationmentioning
confidence: 99%
“…[5][6][7] Other reports suggest roles for HO-1 in defence from viraemia, from oxidant stress, in inflammation and in cardiovascular disease. 8,9 Notably, there are several reports linking HO-1 with cancer, possibly via interactions with VEGF, 10,11 suggesting a role in angiogenesis. 12 Increased expression of HO-1 in prostate tissue and a prostate cancer cell line have been reported 13,14 but there are no reports of plasma HO-1 in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-196 is able to repress oxidative damage by targeting the transcription regulator protein Bach1 [48]. Bach1 is a well-established repressor of the heme oxygenase 1 (HMOX1) gene [49,50], a major cytoprotective enzyme with antioxidant and anti-inflammatory activities [51][52][53]. miR-196 induction downregulates Bach1 and upregulates HMOX1 in human hepatoma 9-13 cells [54].…”
Section: Roles Of Mirnas In Virus-induced Hccmentioning
confidence: 99%
“…The putative 5′ noncoding region is required for replication of HCV RNA [57,58] and possibly contributes to liver tropism of HCV by accelerating binding of ribosomes to viral RNA to stimulate HCV translation [59]. miR-122 antagomir can inhibit replication of HCV, abundance of HCV core RNA, and expression of HCV nonstructural proteins (NS3 in CNS3 cells and NS3-5B in 9-13 replicon cells), in a time-and dosedependent manner [51,[60][61][62][63]. These findings are suggestive of miR-122 as a potential target for antiviral interventions in HCV patients [37,57,[64][65][66][67].…”
Section: Roles Of Mirnas In Virus-induced Hccmentioning
confidence: 99%